Pengaruh Leverage, Profitabilitas, Ukuran Perusahaan, Umur Perusahaan, dan Likuiditas Terhadap Pengungkapan Islamic Social Reporting (ISR) - Alfia Nur Azizah; Dirvi Surya Abbas; Hamdani, Hamdani; Mohamad Zulman Hakim (Pusat Riset dan Inovasi Nasional, 2022)
This research was conducted using secondary data on financial statements that have been published through the official website of each bank by downloading financial report data. The population in this study are Islamic commercial banks in Indonesia in 2015-2020. By using non-probability sampling method, the total sample obtained in this study is 36 data from 6 Islamic commercial banks. The analytical method used in this study is multiple regression analysis using Eviews software version 10 and Microsoft Excel 2016. Based on the research, it shows that leverage, profitability, firm size, firm age, and liquidity together have an influence on the disclosure of Islamic social reporting ( ISR).